Dinâmicas do terceiro setor no Brasil: Trajetórias de criaç\~ao e fechamento de organizaç\~oes da sociedade civil de 1901 a 2020 - Janine Mello; Ana Camila Ribeiro Pereira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This study aimed to systematize and present data on the creation and closure of Brazilian civil society organizations (CSOs) from 1901 to 2020, based on the National Registry of Legal Entities (CNPJ) database provided by the Brazilian Secretariat of the Federal Revenue (SRFB). The exposed results constitute an unprecedented survey encompassing the set of more than one million organizations created in the last 120 years in the country and distributed throughout the national territory.
Keywords: Q10; Q15; 330; civil society; third sector; nonprofit organizations; Brazil